IMPLEMENTASI KEBIJAKAN KERJASAMA TEMPAT PELELANGAN IKAN DENGAN KOPERASI UNIT DESA MINA JAYA DI DINAS KELAUTAN DAN PERIKANAN KABUPATEN KENDAL - Fajar Azis Pramudya; Sri Suwitri; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
There are 4 Fish Auction Place (TPI) in Kabupaten Kendal. The management is done by working with the Village Unit Cooperatives (KUD) Mina Jaya based on article 8 of Regulation No.10 of 2010 regarding Management and Retribution TPI in Kendal. The problem that occurs is the role of middlemen. It is very detrimental to local revenues as the fishermen do not go to the TPI auction fees. The purpose of this study was to determine how the implementation of cooperative management of TPI in Kendal with KUD Mina Jaya Local Regulation No.10 of 2010 regarding Management and Retribution TPI in Kendal; identify factors supporting and inhibiting the activities of the fish auction in Kendal. This study uses a type of qualitative research with research subjects, among others, the Department of Marine and Fisheries officials Kendal, Employees of KUD Mina Jaya and fishing communities at TPI Kendal district.